Effectiveness of height of shear wall stiffening in moment resisting frame-shear wall, dual structural system - Azam, Shaik Kamal Mohammed; Hosur, Vinod (Journal of Structural Engineering, 2024)
The dual structural system consisting of special moment resisting frame (SMRF) with the concrete shear wall stiffening has better seismic performance due to improved lateral stiffness and lateral strength. A well designed system of shear walls in a building frame improves its seismic performance significantly. In the shear wall-moment resisting frame dual structural system, the shear wall stiffening is generally provided for the full height of the structure. In the current study, the shear wall stiffening is increased in stages up-to the full height of the structure to study significance of contribution of shear wall stiffness to the lateral strength and lateral stiffness of the structure. The elastic (response spectrum analysis) as well as in-elastic (nonlinear static pushover analysis) analyses are carried out for the evaluation of seismic performance. The results of the study indicate that the provision of shear wall stiffening beyond 50% of the height of the structure does not contribute significantly to the lateral strength and lateral stiffness of the structure.